EFEKTIVITAS EKSTRAK TUMBUHAN MENGELIMINASI Clavibacter michiganensis Saubsp. Michiganensis DAN MEMPERTAHANKAN MUTU FISIOLOGIS BENIH TOMAT - Aprizal Zainal; Aswaldi Anwar; Sudarsono .; Satriyas Ilyas; Giyanto . (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2011)
The objectives of the experiment were to evaluate effectiveness of seed treatments to eliminate Cmm of infected tomato seed lot, evaluate physiological quality of Cmm infected tomato seed lot after treatments with plant extracts. The research used curcuma rhizomes, betel vine leaf extract, cinnamon and clove oil to eliminate Cmm in tomato seed. Part of the seeds were dipped in either suspension of curcuma rhizomes, betel vine leaf extract, cinnamon and clove oil for 20 minutes and the others were matriconditioned using a mixture of burned rice hull (at 22 0C and RH 60-70%) plus either of plant extracts or oils. Elimination of Cmm from infected seeds was observed 10 days after treatments, and physiological seed qualities were evaluated before and after seed treatments. Results of the experiment indicated, dipping infected seeds in either 5% of curcuma, betel vine extract, cinnamon oil or 0.5% of clove oil suspension or matriconditioning plus either these extracts, eliminated 99% of infected Cmm on tomato seeds. Seed treatments using plant extracts for elimination of Cmm did not reduce seed germination, germination rate, vigor index, and did not increase time to reach 50% total germination (T50) of infected tomato seed except the seed treatment by using 5% cinnamon oil with or without matriconditioning.Key words: plant extracts, physiological quality, seed viability, vigor